The Metaverse and Terrorism: threats and Challenges - Weimann, Gabriel (Perspectives on terrorism, 2023)
The metaverse is currently the leading hype in the digital world because of its seemingly infinite potential and possibilities. Large corporations are drawn to the metaverse because it appears as the cutting edge of digital and technological developments. The metaverse is presented by communication technology companies as the next Internet, a leap towards a universe of boundless, interconnected virtual communities. However, there are many potential risks and challenges that the metaverse raises, including technical, legal, security, business, tax, privacy, security, and users’ well-being and safety (among many others). Cyber-savvy terrorists have been highly resourceful in adapting and applying online platforms and have taken advantage of every new development, platform, and application. Based on their past record, it is reasonable to assume that the metaverse is a new dimension that terrorists and violent extremists are poised to study, examine, and possibly utilise. This research article explores some potential uses of the metaverse by terrorists and suggests preemptive measures to minimise the risks of them doing so. If the advancement of the metaverse or similar developments is inevitable, we should consider risks and abuses and think more carefully about them when moving forward.